THE OPTIMALIZATION OF LOCATION TRANSPORT JUNCTIONS (Perner's Contacts, 2010)
This article is focused on the issue of deployment of transport junctions and other transport network, using modern optimization algorithms. The main emphasis is placed on genetic algorithm operating on the principle of location with simple hub allocation without capacity constraints and simulation of evolutionary processes applied to the transport nodes.
Keywords: algorithm; hub; location; material flow optimization